CBT Made Simple / Second Edition - Josefowitz Nina; Myran David (2021)
This book (CBT) is a highly effective, evidence - based treatment for mental health disorders. Foreword, Introduction, CBT Foundation, Use CBT Theory to Understand Your Clients, Focus on Your Clints' Problems and Strenggths, Develop Goals for Therapy, Structure Your Sessions, Understand Your Clients' Problems, Identity Your Clients' Feelings and Physical Reactions and Behaviors, My Clients have so many Thoughts: Which Do I Focus On?, Identity Your Clients' Thoughts, Cognitive and Behavioral Interventions, Look for Evidence and Create Balanced Thoughts, Problem Solving: Finding a Better Way, Behavioral Activation: Action Plans for Depression, Exposure Therapy: Clients Face Their Fears, Working with Core Beliefs, Underlying Assumptions and Behavioral Experiments, CBT in Action, Treatment Guidelines and Suzanne and Raoul's Therapy, Acknowledgements, Appendix: Answers to YOUR TURN! Exercises, References, Index.